2015
DOI: 10.1016/j.sbspro.2015.04.068
|View full text |Cite
|
Sign up to set email alerts
|

Achievements of Numeracy Abilities to Children with Down Syndrome: Psycho-Pedagogical Implications

Abstract: The paper addresses the issue of children with Down syndrome and psycho-pedagogical implications in the present. Down syndrome is the most common biological cause of intellectual disability. This intervention study was conducted to explore the effectiveness of using the tablet as a learning tool in teaching mathematics to children with Down syndrome. Also, to explore the extent to which children with Down syndrome are able to learn counting elementary mathematics concepts, such as the addition operation or sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…They also learn by observing the activities of others (Reed, Staytom, Stott, & Truzoli, 2011) and when they are rewarded for their actions (Kogan et al, 2009). Finally, the use of multimedia helps children with DS to develop cognitive processes that facilitate symbolic thinking (Agheana & Duță, 2015).…”
Section: Down Syndrome and Learningmentioning
confidence: 99%
“…They also learn by observing the activities of others (Reed, Staytom, Stott, & Truzoli, 2011) and when they are rewarded for their actions (Kogan et al, 2009). Finally, the use of multimedia helps children with DS to develop cognitive processes that facilitate symbolic thinking (Agheana & Duță, 2015).…”
Section: Down Syndrome and Learningmentioning
confidence: 99%
“…From the perspective of quality of life, literacy, the ability of reading and writing as well as numeracy, the concept of the number are important in day to day life and facilitate the vocational opportunities as well as chances of independent living in individuals with DS. 79,80 There is a spectrum of attainment of literacy skills in children with DS. When compared with mental age-matched children, the language was a stronger predictor of reading ability in contrast to cognition in the group with DS.…”
Section: Academicsmentioning
confidence: 99%
“…However, there are challenges in verbal processing skills that lead to deficits in word attack skills. 79 Individuals with DS can attain simple skills in numeracy but a study suggested that unlike reading this cannot be retained into adolescence and adulthood. 81 Research has also shown that children with DS can improve on these skills if appropriate strategies are used that employ their stronger visual learning skills.…”
Section: Academicsmentioning
confidence: 99%
“…Children with Down Syndrome do not pay attention when there is a teaching and learning process in the classroom, are not ready to learn, do not understand what is learned and are less mature. Their thinking does not commensurate with their age and they cannot remember what is being taught and learned (Agheana& Duţă, 2015;Trezise, Gray, Taffe, & Sheppard, 2014;Wan Fatimah Wan Ahmad, Hidayatun Nafisah Isa Muddin, & Afza Shafie, 2014).…”
Section: Down Syndromementioning
confidence: 99%